PARTICIPATORY DEMOCRACY AND MODERN TECHNOLOGIES IMPLEMENTATION OF PUBLIC INTEREST AT THE LOCAL LEVEL - Чабан, О.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article examines the concept of participatory democracy, the supporters of which are actively seeking channels of effective involvement of citizens into the process of elaboration and adoption of political and administrative decisions. Special attention is paid to the analysis of the international experience of the implementation of „participatory budgeting” as one of the structures of production and protection of public interest at the local level.